Nuclear equation of state effects on the r-mode instability of neutron stars - Moustakidis, Ch. C. (HNPS Advances in Nuclear Physics, 2012)
We study the effect of nuclear equation of state on the r-mode instability of a rotating neutron star. We consider the case where the crust of the neutron star is perfectly rigid and we employ the related theory. The effects of the density dependence of the nuclear symmetry energy on r-mode instability properties are presented and analyzed. A comparison of theoretical predictions with observed neutron stars in low-mass X-ray binaries is also performed and analyzed.